Demographic Characteristics, Health Behaviors before and during Pregnancy, and Pregnancy and Birth Outcomes in Mothers with different Pregnancy Planning Status - Cheng, Tuck Seng (Prev Sci, 2016)
Studies on pregnancy intentions and their consequences have yielded mixed results. Here, we comprehensively analyzed the maternal characteristics, health behaviors before and during pregnancy, as well as pregnancy and birth outcomes, across three different pregnancy planning status in 861 women participating in an ongoing Asian mother-offspring cohort study. At 26-28 weeks’ gestation, the women’s intention and enthusiasm towards their pregnancy were used to classify their pregnancy into planned or unplanned, and unplanned pregnancy was further subdivided into mistimed or unintended. Data on maternal characteristics, health behaviors, and pregnancy outcomes up to that stage, were recorded. After delivery, birth outcomes of the offspring were recorded. Linear and logistic regression analyses were performed. Overall, 56% had a planned pregnancy, 39% mistimed, and 5% unintended. Compared to women who planned their pregnancy, women with mistimed pregnancy had higher body mass index, and were more likely to have cigarette smoke exposure and less likely to have folic acid supplementation. At 26-28 weeks’ gestation, unintended pregnancy was associated with increased anxiety. Neonates of mistimed pregnancy had shorter birth length compared to those of planned pregnancy, even after adjustment for maternal baseline demographics. These findings suggest that mothers who did not plan their pregnancy had less desirable characteristics or health behaviors before and during pregnancy, and poorer pregnancy and birth outcomes. Shorter birth length in mistimed pregnancy may be attributed to maternal behaviors before or in the early stages of pregnancy, therefore highlighting the importance of preconception health promotion and screening for women of child-bearing age.